DESIGNING E-PON TO ENCOURAGE STUDENTS AT ELEMENTARY SCHOOL IN LEARNING NUMBERS - Nugraha, Rizki Fajar; Salam, Urai; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research is to design an e-presentation as a multimedia product that can be used in learning numbers. The method of this research is development research which consists of four phases; analysis, design, develop and implement (ADDI) as the phases in designing e-PoN. e-PoN is an electronic presentation containing materials about numbers. e-PoN provides four menus as the main features. Each menu presents different types of content regarding the topic. The respondents in this research are the fourth-grade students and the English teacher of SDN 34 Pontianak Kota. The researcher also involved some English teacher from another school as a facilitator to find out whether e-PoN can be used in learning number through a multimedia rubric. The multimedia rubric was developed by following criteria for assessing the multimedia project. The multimedia rubric results 88% which indicates that e-PoN can be used as a multimedia product for encouraging elementary school students in learning numbers. Keyword: e-Presentation, Development Research, Learning Number